Innovative sustainable bioreactor-in-a-granule formulation of Trichoderma asperelloides - Silva, Lucas Guedes [UNESP]; Camargo, Renato Cintra; Mascarin, Gabriel Moura; Favaro, Camila Patrícia; Nunes, Peterson S. O.; Farinas, Cristiane Sanchez; Ribeiro, Caue; Bettiol, Wagner [UNESP] (Springer Nature, 2024)
Abstract: The advancement of fungal biocontrol agents depends on replacing cereal grains with low-cost agro-industrial byproducts for their economical mass production and development of stable formulations. We propose an innovative approach to develop a rice flour-based formulation of the beneficial biocontrol agent Trichoderma asperelloides CMAA1584 designed to simulate a micro-bioreactor within the concept of full biorefinery process, affording in situ conidiation, extended shelf-life, and effective control of Sclerotinia sclerotiorum, a devastating pathogen of several dicot agricultural crops worldwide. Rice flour is an inexpensive and underexplored byproduct derived from broken rice after milling, capable of sustaining high yields of conidial production through our optimized fermentation-formulation route. Conidial yield was mainly influenced by nitrogen content (0.1% w/w) added to the rice meal coupled with the fermentor type. Hydrolyzed yeast was the best nitrogen source yielding 2.6 × 109 colony-forming units (CFU)/g within 14 days. Subsequently, GControl, GLecithin, GBreak-Thru, GBentonite, and GOrganic compost+Break-Thru formulations were obtained by extrusion followed by air-drying and further assessed for their potential to induce secondary sporulation in situ, storage stability, and efficacy against Sclerotinia. GControl, GBreak-Thru, GBentonite, and GOrganic compost+Break-Thru stood out with the highest number of CFU after sporulation upon re-hydration on water-agar medium. Shelf-life of formulations GControl and GBentonite remained consistent for > 3 months at ambient temperature, while in GBentonite and GOrganic compost+Break-Thru formulations remained viable for 24 months during refrigerated storage. Formulations exhibited similar efficacy in suppressing the myceliogenic germination of Sclerotinia irrespective of their concentration tested (5 × 104 to 5 × 106 CFU/g of soil), resulting in 79.2 to 93.7% relative inhibition. Noteworthily, all 24-month-old formulations kept under cold storage successfully suppressed sclerotia. This work provides an environmentally friendly bioprocess method using rice flour as the main feedstock to develop waste-free granular formulations of Trichoderma conidia that are effective in suppressing Sclerotinia while also improving biopesticide shelf-life. Key points: • Innovative “bioreactor-in-a-granule” system for T. asperelloides is devised. • Dry granules of aerial conidia remain highly viable for 24 months at 4 °C. • Effective control of white-mold sclerotia via soil application of Trichoderma-based granules.
Keywords: Biocontrol agent; Bioprotectant; Granule formulation; Solid-state fermentation; Trichoderma; White mold